Utilizing different aquatic resources for livelihoods in Asia : (FAO/IIRR/IDRC/NACA/ICLARM, 2001)
This is a resource book on the utilization of a wide range of aquatic ecosystems. This resource book consists of a compilation of proven experiences from Asia that are totally field-derived. Thirty-seven participants from 12 countries worked closely with a production team of editors, artists and desktop publishing staff in the production of this book